KIDNEY MICROANATOMY OF WHITE RATS ON THE ADMINISTRATION OF ETHANOL EXTRACT OF Spatholobus littoralis STEM ACUTE DOSE - Rousdy, Diah; Azkiya, Tiara; Wardoyo, Elvi Rusmiyanto Pancaning (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
Tampala bajakah stem (Spatholobus littoralis Hassk) is empirically used by the Indonesian people to recover from disease and maintain health, but the use of tampala bajakah has not been tested for doses that are safe for consumption. The purpose of this study was to determine the type of damage caused by acute doses of bajakah tampala stem extract on white rat kidney microanatomy (Rattus norvegicus Berkenhout). This study used bajakah stem derived from Ambawang, extraction using ethanol solvent, and Wistar strain white rat (± 150g) test as a test animal. The method used a Complete Randomized Design with 4 treatments namely normal control using distilled water, treatment of doses of 300, 2000, and 5000 mg/kg BW of bajakah tampala stem extract. Each group was given 5 replicates. The extract was shown in a single dose orally and observations were made for 14 days. The results obtained that doses of 2000 and 5000 mg/kg BW caused damage to white rat kidney tissue in the form of microanatomy dilatation of tubules and loss of the brush border, and doses of 300, 2000, and 5000 mg/kg BW caused necrosis and haemorrhage. The most severe damage to kidney microanatomy is the dose of 2000 and 5000 mg/kg BW. The administration of acute doses of bajakah extract has the potential to cause damage to kidney tissue.